A influência da acessibilidade na escolha da rota urbana e do meio de transporte escolar : estudo de caso com os alunos da rede municipal de ensino da cidade de João Pessoa-PB - Abreu, Danilo Wanderley Matos de (2006)
In João Pessoa the study of movements and school transports have been made being just taken in consideration distance aspects, flow and width of streets and sidewalks. Was identified that the students of the municipal net in your great majority are put close to your residences, but they use the motorized transport, partly, influenced by the dangers in the school courses as for the lack of physical conditions of many itineraries. Considering that this process reaches in an unequal way the areas of inclusion of each school, the objective of this work is to evaluate as the accessibility level it can influence on the choice of the route and in the way of the transport used by the municipal net. With this end, a methodology of evaluation of the spaces for pedestrians, developed by Ferreira and Sanches in 1998, and a theory of Space Syntax, developed by Hillier and Hanson in 1984, they were used to confront the users' perception with relationship to the accessibility and to analyze the roads graphically used by the students. The work shows that accessibility has great influence in the choice of the path as well as in the transport type used in the house course to the study place.